2011
DOI: 10.1051/0004-6361/201117076
|View full text |Cite
|
Sign up to set email alerts
|

The 2008 outburst of IGR J17473–2721: evidence for a disk corona?

Abstract: Context. The 2008 outburst of the atoll source IGR J17473-2721 was observed by INTEGRAL, RXTE and Swift. Tens of type-I X-ray bursts were found in this outburst. Aims. Joint observations by INTEGRAL, RXTE, and Swift provide sufficient data to look into the behavior of IGR J17473-2721 at the rising part of the 2008 outburst. The relation between the duration of the bursts and the accretion rate and the nature of the corona producing the observed power-law component can therefore be studied in detail. Methods. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Besides 4U 1908+005 (Aql X−1) and 4U 1608−522 (Gladstone et al 2007), IGR J17473−2721 is thus the third NS XRB observed with hysteresis. There are 32 bursts located in the preceding LHS and 10 bursts in the tail of the HSS and the lagging LHS (Chen et al 2010(Chen et al , 2011Chenevez et al 2011), constituting an entire sample of 42 bursts recorded by RXTE. The long-lived preceding LHS and the large number of burst events occurred in both the preceding and lagging LHSs make IGR J17473−2721 almost unique for probing its corona (Zhang et al 2009) under a circumstance of an outburst evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides 4U 1908+005 (Aql X−1) and 4U 1608−522 (Gladstone et al 2007), IGR J17473−2721 is thus the third NS XRB observed with hysteresis. There are 32 bursts located in the preceding LHS and 10 bursts in the tail of the HSS and the lagging LHS (Chen et al 2010(Chen et al , 2011Chenevez et al 2011), constituting an entire sample of 42 bursts recorded by RXTE. The long-lived preceding LHS and the large number of burst events occurred in both the preceding and lagging LHSs make IGR J17473−2721 almost unique for probing its corona (Zhang et al 2009) under a circumstance of an outburst evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous reports showed that the corona of the system (Figure 3) is most likely located around a largely inclined disk and forms a relatively small opening angle with respect to the surface of neutron star, so that the type-I X-ray bursts can escape from the NS surface without suffering severe Comptonization (Zhang et al 2009;Chen et al 2011). The 30-50 keV decrement reaches a maximum of ∼2 cts/s at the 2-10 keV burst peak, accounting to about half of the 30-50 keV persistent flux.…”
Section: Resultsmentioning
confidence: 99%
“…Kuulkers et al (2009) discuss an X-ray burst from Cen X-4 which appears to have turned the accretion disk into a hot state, although it appears at odds with accretion disk theory. Other examples of influence are bursts that cool the accretion disk corona (Chen et al 2011) and bursts with superexpansion, such as the superburst from 4U 1820-30 (Strohmayer & Brown 2002;Ballantyne & Strohmayer 2004;Keek 2012) and a number of bursts from (candidate) ultracompact X-ray binaries (in 't Zand & Weinberg 2010). During these bursts, episodes exist when the flux is lower than the pre-burst accretion flux.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas may be energized to form a corona via either evaporation (Meyer et al 1994) or magnetic re-connections (Zhang et al 2000). Chen et al (2011) and Chen et al (2011) take advantage of the type-I X-ray bursts from the hard surface of a NS of the NS XRB IGR J17473−2721 to probe the purported corona, under a circumstance of outburst and accompanying spectral evolution, find that • The corona seems to be located above the disk, but not around the NS, so that emission from type-I X-ray bursts can escape from the NS surface without suffering Comptonization.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, roughly one third of the bursts are PRE bursts (Galloway et al 2008). In this paper, we report the results by analysis all of the RXTE/PCA observations data on Aql X-1 using the similar procedure in Chen et al (2011).…”
Section: Introductionmentioning
confidence: 99%